New necessary conditions for optimal control problems in discontinuous dynamic systems - Kostina, Ekaterina; Kostjukova, Ol'ga I.; Schmidt, Werner H. (System modeling and optimization, 2013)
In the paper we derive new necessary optimality conditions for optimal control of differential equations systems with discontinuous right hand side. The main attention is paid to a situation when an optimal trajectory slides on the discontinuity surface. The new conditions, derived in the paper, are essential and do not follow from any known necessary conditions for such systems.
Gesehen am 03.08.2018